Physics Contributions Does help structures play a role in reducing the variation of dwell time in IPSA planning for gynaecological brachytherapy application? - Jamema, Swamidas; Mahantshetty, Umesh; Deshpande, DD; Sharma, Smriti; Shrivastava, SK (Journal of Contemporary Brachytherapy, 2011)
Purpose : To report our experience of dosimetric comparison of IPSA and manual plans, with a focus on the use of help structures (HS) during optimization. Material and methods : 33 patients who underwent MR image-based HDR intracavitary-brachytherapy for cervix cancer based on GYN-ESTRO recommendations were selected for evaluation. Tandem/ovoid (T/O) and Vienna applicators were used. HS of diameter of 5 mm were drawn around the tandem/needles/ovoid and ring. Three plans were generated: manual optimized plan (MOPT), IPSA without help structures (IPSA_woHS) and IPSA with help structures (IPSA_wHS). Dose-volume parameters and the loading pattern were evaluated. Results : IPSA produced superior and conformal plans as compared to MOPT. For T/O, the use of HS did not make significant impact in the dose-volume parameters and in the loading of tandem and ovoids, however steep variation was found in the individual dwell time. In case of Vienna applicator, inclusion of HS in the optimization made a significant impact in loading of needles. The percentage ratio of total time of needles to the tandem (TN/T%) was found to be 14 ± 2.5, 53 ± 9, 22 ± 6 for MOPT, IPSA_woHS and IPSA_wHS, respectively, which implies that in IPSA_woHS the dwell time in needles were half of the dwell time in the tandem, while in MOPT the needles were loaded only in 14%, and in IPSA_wHS it was 22% of the dwell time of tandem. Inclusion of HS in the optimization has reduced the contribution of dwell time of needle in IPSA_wHS. The individual variation of dwell time was also reduced in IPSA_wHS, however drawing of HS is a time consuming procedure and may not be practical for a routine practice. Conclusion : The role of HS was evaluated for IPSA for T/O and Vienna-applicator, the use of HS may be beneficial in case of combined intracavitary – interstitial approach.